Anatomical Investigation and GC/MS Analysis of 'Coco de Mer', Lodoicea maldivica (Arecaceae). Issue 11 (13th November 2020) - Giuliani, Claudia; Pieraccini, Giuseppe; Santilli, Carolina; Tani, Corrado; Bottoni, Martina; Schiff, Silvia; Fico, Gelsomina; Papini, Alessio; Falsini, Sara
Abstract: Lodoicea maldivica (J.F.Gmel.) Pers. (Arecaceae), 'Coco de Mer', is a palm, growing as endemic in the Seychelles islands. Its fruit weighs up to 20 kg and is characterized by a fleshy and fibrous envelope surrounding the nutlike portion. The present work combines a morpho‐anatomical and a phytochemical analysis of the fruit exocarp and mesocarp. The exocarp is composed by a layer of palisade cells. The mesocarp is characterized by vascular bundles and by sclereids. In the aerenchyma, the internal zone of the mesocarp, cells aggregates were positive to phenols, while idioblasts were positive to terpenes. We performed a GC/MS analysis with a semi‐quantitative relative amount calculation of the recorded compounds. The GC/MS essential oil profile revealed the dominance of acyclic sesquiterpenoids (53.95 %), followed by bicyclic sesquiterpenoids (31.69 %), monoterpenes (11.89 %) and monocyclic sesquiterpenoids (2.44 %). The terpenes detected in higher amounts, β ‐caryophyllene and bicyclogermacrene, are known for activity against insect larvae, but have been proposed as antiviral candidates against SARS‐CoV‐2. The third compound in amount, aromadendrene, is active against bacteria and, again, known to possess insecticidal properties. Abstract :